O ensino da matemática financeira através de interações numéricas e computacionais - Sampaio, Francisco Ricardo Moreira (2013)
The Financial Mathematics permeates social relations, to the extent that it operates significantly in daily life. The Law of Guidelines and Bases of Education, called LDB, in Brazil, raises the civic education of the student and the Enem (A Brazilian National Exam for Students from highschool), as the assessment requires the student's effective learning of that knowledge. Despite its importance, we find difficulties in the effective teaching of Mathematical Finance. This paper aims to present the construction and use of two applications: the Easy interest, “Juro Fácil” in Portuguese, built in Excel spreadsheet and the Ruler Financial or “Régua Financeira”, Software in GeoGebra. These applications assist in troubleshooting Financial Mathematics. The Easy Ruler contributes mainly in the interest calculation, Pegasus implementing the numerical method for the determination of the roots of transcendental equations, which do not allow the analytical calculation of the same. The Financial Ruler explains the mechanical displacement of the instalments loan under the influence of an interest rate, or the values as they move over time.